Pengaruh Financial Leverage, Profitabilitas Dan Besaran Penawaran Saham Terhadap Initial Return - Darpius Darpius; Henri Agustin; Vita Fitria Sari (Universitas Negeri Padang, 2019)
This research aimed to give evidence about influence of financial leverage, profitability, and percentage of share which initial return IPO in Indonesia Stock Exchange in the year 2011-2017. Population used in this research is companies that go public on the Indonesia Stock Exchange by taking a sample of firms in 2011-2017, while the sample is 127 companies, with a purposive sampling technique. Type of data used are secondary data. Data collection method used is documentation from www.idx.com and companies website. Analysis tool used is multiple linear regression. The results of this study are (1) financial leverage have significant positive to company’s stock initial return (2) profitability and percentage of share has no effect to the company’s stock initial return.